The Implementation Of Character Education To Prevent Bullying In Schools: A Case Study Of New Students At SMA Al Azhar 9 Yogyakarta - M Mahbubi (Journal of Education and Learning Sciences, 2024)
This study explores the implementation of character education as a preventive strategy against bullying among new students at SMA Islam Al Azhar 9 Yogyakarta. Recognizing the importance of fostering a positive and inclusive school environment, the research examines how the institution promotes healthy relationships through personalized student support, peer mentoring, and inclusive activities. These efforts aim to create a safe and welcoming atmosphere that reduces instances of bullying while enhancing student well-being and social integration. Data collection involved in-depth interviews with key stakeholders, including the Vice Principal for Student Affairs, the Guidance Counselor, and the Head of the School, alongside observational methods to assess the implementation of character education strategies in daily school activities. The findings suggest that SMA Islam Al Azhar 9 Yogyakarta adopts a proactive and continuous engagement approach, ensuring that new students feel supported and integrated into the school community. This method significantly contributes to preventing bullying by emphasizing relationship-building, empathy, and mutual respect. The study underscores the effectiveness of character education programs in shaping school culture and minimizing bullying incidents. By implementing structured mentoring systems and interactive initiatives, the school cultivates a culture of care and responsibility among students. The results offer valuable insights for other educational institutions seeking to address bullying through character development. Future research is recommended to examine the long-term impact of such programs on student behavior, school climate, and overall academic success